IgE sensitization to Anisakis pegreffii in Italy: Comparison of two methods for the diagnosis of allergic anisakiasis. (July 2017) - Mattiucci, S.; Colantoni, A.; Crisafi, B.; Mori‐Ubaldini, F.; Caponi, L.; Fazii, P.; Nascetti, G.; Bruschi, F.
SUMMARY: IgE sensitization to Anisakis pegreffii in Italian subjects suffering from gastro‐allergic anisakiasis (GAA) (N=5), or showing chronic urticaria (CU+) after fish consumption (N=100), was investigated. A control group (N=5) was also included. IgE response was analysed by immunoblotting (WB) assay, using both excretory/secretory products (ESPs) and crude extract (CE) of A. pegreffii larvae. The results were compared with those achieved by the conventional immunological method for Anisakis allergy (ie, immunoCAP). Among the 110 subjects, 28 showed IgE positivity with both WB and iCAP methods; 13 proved IgE reactivity, in WB assay, to ESP antigens of A. pegreffii, here provisionally indicated as Ani s 1 ‐ like, Ani s 7 ‐ like, Ani s 13 ‐ like; only 15 sera have shown IgE‐WB reaction to Ani s 7 ‐ like and Ani s 13 ‐ like. iCAP and WB exhibited a high concordance value (κ=1.00) when iCAP value was <0.35 (negative result) and >50.0 (positive result). In the sera samples recorded as positive to Anisakis allergy, Ani s 1 ‐ like was responsible for 46.4% of the sensitivity, while Ani s 7 ‐ like and Ani s 13 ‐ like for 100%. They could be considered as major antigens in the diagnosis of allergic anisakiasis caused by A. pegreffii .